2011
DOI: 10.1111/j.1752-7325.2010.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries preventive effects of xylitol-based candies and lozenges: a systematic review

Abstract: This research demonstrates the need for well-designed randomized clinical studies with adequate control groups and high compliance by the subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…suggests that xylitol could have tooth-surface-specific cariespreventive effects (Antonio et al, 2011) but did not examine coronal vs. root surfaces. Furthermore, most evidence of xylitol for caries prevention is derived from studies on children and adolescents with no root surfaces at risk.…”
mentioning
confidence: 99%
“…suggests that xylitol could have tooth-surface-specific cariespreventive effects (Antonio et al, 2011) but did not examine coronal vs. root surfaces. Furthermore, most evidence of xylitol for caries prevention is derived from studies on children and adolescents with no root surfaces at risk.…”
mentioning
confidence: 99%
“…A study by Ly et al [12] has proved that ingesting 10.32 g of xylitol in chewing gum daily results in a significant reduction of the SM count in resting saliva and dental plaque and that there is an inverse proportion between the frequency of using xylitol chewing gum and the bacteria count. Antonio et al [17], in their literature review regarding candies and lozenges, have noted that such means of applying xylitol may decrease the increment of caries, however they do not appear effective toward the interproximal surfaces of teeth. Shortterm application of chewing gum reduces the SM count in saliva but does not affect the composition of oral microbiota [32].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the sort of xylitol-containing product and the manner of its consumption (chewing gum, lozenges, syrup, etc.) was significant [17]. The impact of additives to products containing xylitol on the development of oral microbiota is also worth noting.…”
mentioning
confidence: 99%
“…After excluding studies that did not allow an adequate interpretation, only 3 studies were included in the meta-analysis, and the results indicated a caries-preventive effect of evaluated products. 43 According to Huebner et al, 44 literature reviews on the use of xylitol are important because the dissemination of research-based information on xylitol to dentists in clinical practice is quite limited. As a result, published evidence on mother-to-child transmission of S. mutans or xylitol efficacy is practically unknown, which limits the interest on the action of this polyol as well as the emergence of new research.…”
Section: Discussionmentioning
confidence: 99%